Shining a spotlight on the dangerous consequences of conspiracy theories. (October 2022) - Jolley, Daniel; Marques, Mathew D.; Cookson, Darel
Abstract: The COVID-19 pandemic has illuminated how conspiracy beliefs–that explain important events as the secret actions of the powerful–can severely impact health choices (such as reduced infection-prevention behaviours). However, the consequences of conspiracy beliefs span far beyond the topic of COVID-19. This review shines a spotlight on how conspiracy beliefs could impact public and personal health (e.g., vaccine uptake), democratic citizenship (e.g., political engagement), intergroup relations (e.g., prejudice and discrimination), and may inspire violence and extremism. We argue that conspiracy beliefs are likely to have the power to mobilise citizens in ways detrimental to a smooth-running society. We conclude the review by offering a range of fruitful avenues for future investigation.